Hydroclimatology, modes of climatic variability and stream flow, lake and groundwater level variability. - McGregor, Glenn (Progress in Physical Geography: Earth and Environment, 2017)
Hydroclimatology is an expansive discipline largely concerned with understanding the workings of the hydrological cycle in a climate context. Acknowledging this, and given the burgeoning interest in the relation between climate and water in the context of working towards an improved understanding of the impacts of climatic variability on water resources, this progress report turns its attention to the connection between large-scale modes of climatic variability and hydrological variability in streams, lakes and groundwater. A survey of the recent literature finds that a plethora of teleconnection indices have been employed in the analysis of hydrological variability. Indices representing modes of climatic variability such as El Niño Southern Oscillation, the North Atlantic Oscillation, the Pacific North America pattern, the Pacific Decadal Oscillation and Atlantic Meridional Oscillation dominate the literature on climatic and hydrological variability. While examples of discernible signals of modes of climatic variability in stream flow and lake and groundwater level time series abound, the associations between periodic to quasi-period oscillations in atmospheric/ocean circulation patterns and variability within the terrestrial branch of the hydrological are far from simple, being both monotonic (linear and non-linear) and non-monotonic and also conditional on period of analysis, season and geographic region. While there has been considerable progress over the last five years in revealing the climate mechanisms that underlie the links between climatic and hydrological variability, a bothering feature of the literature is how climatic and hydrological variability is often viewed through a purely statistical lens with little attention given to diagnosing the relationship in terms of atmosphere and ocean physics and dynamics. Consequently, significant progress remains to be made in obtaining a satisfactory hydroclimatological understanding of stream flow, lake and groundwater variability, especially if hydroclimatological knowledge is to be fully integrated into water resource management and planning.